Binocular summation in high and low contrast letter acuities - Yu, Deyue; Watson, Emily (Frontiers in Neuroscience, 2023)
Binocular summation, a well-known phenomenon in letter acuity measurement, refers to the improvement in visual performance when viewing with both eyes compared to one eye alone. The present study aims to assess the relationship in binocular summation between high and low contrast letter acuities, and examine whether baseline measure (binocular summation at either high or low contrast) is predictive of the change in binocular summation between contrast conditions. Corrected high and low contrast letter acuities were assessed monocularly and binocularly in 358 normal vision observers aged 18–37 years using Bailey-Lovie charts. All observers had high contrast acuities (both monocular and binocular) of 0.1 LogMAR or better and no known eye disease. Binocular summation was calculated as the difference in LogMAR between the better eye acuity and binocular acuity. We found that binocular summation was present at both contrast levels (0.044 ± 0.002 LogMAR for high and 0.069 ± 0.002 LogMAR for low contrast) with higher magnitude of summation at low contrast, and declined with increasing interocular difference. There was a correlation in binocular summation between high and low contrast. The difference in binocular summation between the two contrast levels was found to be correlated with the baseline measurement. Using common commercially available letter acuity charts, we replicated the findings on binocular acuity summation in normally sighted young adults for both high and low contrast letters. Our study revealed a positive relationship in binocular acuity summation between high and low contrast, and an association between a baseline measure and the change in binocular summation between contrast levels. These findings may serve as a reference in clinical practice and research when high and low contrast binocular summations are measured in assessing binocular functional vision.